THE EFFECT OF JOB DESCRIPTION CLARITY AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE WITH WORK DISCIPLINE AS AN INTERVENING VARIABLE AT MNC FINANCE AREA ACEH - Syafrizal Lubis; Yeni Absah; Evawany Yunita Aritonang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of job description clarity and work motivation on employee performance, with work discipline as an intervening variable at PT MNC Finance Aceh Area. The background of this study is based on the post-pandemic phenomenon that causes unclear division of tasks and responsibilities between divisions, low work motivation, and inconsistency in employee discipline, which impacts target achievement and work effectiveness. This study uses a path analysis method with a census approach, involving 60 employee respondents at PT MNC Finance Aceh Area. The results show that job description clarity has a positive effect on employee performance, although the direct effect is not significant. However, the indirect effect through work discipline makes a strong contribution to improving performance. Work motivation also has a positive but relatively weak effect on performance, and a positive effect on work discipline with a smaller effect than job description. Work discipline is proven to have a positive and significant effect on employee performance, and acts as a partial intervening variable that strengthens the relationship between job description clarity and work motivation on performance. Overall, the research results confirm that improving employee performance at PT MNC Finance Area Aceh can be achieved through clear job descriptions, increasing motivation, and consistent work discipline development.